Pengaruh Harga, Citra Merek dan Kualitas Pelayanan terhadap Loyalitas Pelanggan Di Rumah Makan Bu Rupa di Tanah Merah - Laylatus Sa'adah; Oktaviana Arisinta; Yusrianto Sholeh (Universitas Batanghari, 2022)
Indonesia consists of various ethnic groups, languages and different religions. In addition to having a dense population and large area, Indonesia has a natural area that supports the second largest level of biodiversity in the world. Indonesia has 34 provinces where each province has a different culture and special food. Indonesia is a country that is famous for its culinary fields, there are many kinds of Indonesian food and drinks, because Indonesia is rich in its unique cooking spices. The purpose of this study was to determine the effect of price, brand image, and service quality on customer loyalty at Bu Rupa's restaurant in Tanah Merah. The population in this study were all consumers at Mrs. Rupa's restaurant, so the sample used was 50 respondents. The results of this study indicate that price has no effect on customer loyalty, as evidenced by the Tcount value of 1.784 and a significant value of 0.81 so that it is said to be significant Ha is rejected and Ho is accepted. Brand image has an effect on customer loyalty, which is evidenced by the Tcount value of 5.519 and a significant value of 0.000 so that it is said to be significant, then Ha is accepted and Ho is rejected. Service quality has no effect on customer loyalty, as evidenced by the Tcount 1.664 and a significant value of 0.103, then Ha is rejected and Ho is accepted. The next result is to prove that price and brand image affect customer loyalty with a calculated F value of 11,515 and a significant value of 0.000 so that the value is said to be significant, then Ha is accepted and Ho is rejected, meaning that price, brand image and service quality have a positive influence simultaneously on customer loyalty.